From classroom to market: The role of brand identity and local cultural values in building customer loyalty for vocational teaching factory products - Ratih Puspitorini Yekti Ambarkahi; Fredy Eka Ardhi Pratama; Ponti Primastuti Aulia Nugraheni; Pascawati Savitri Universitasari; Dhanang Eka Putra (FOUNDAE (Foundation of Advanced Education), 2026)
Teaching Factory (TEFA) programs are designed to connect classroom-based vocational education with real market production, positioning polytechnics as hybrid institutional–commercial actors within regional innovation ecosystems. However, sustaining the commercial viability of TEFA products remains a structural challenge. This study investigates the role of brand identity and local cultural values in strengthening customer loyalty toward TEFA products at Politeknik Negeri Jember. Employing a quantitative explanatory design with path analysis on data collected from 215 respondents, the study examines both direct and mediated relationships among brand identity, perceived cultural values, and customer loyalty. The results indicate that brand identity significantly influences customer loyalty directly (β = 0.412, p < 0.01) and indirectly through local cultural values (β = 0.153, p < 0.01), with the model explaining 46.1% of the variance in loyalty. These findings suggest that culturally embedded branding enhances institutional credibility and supports the transition from educational production to sustainable market engagement. The study contributes to the understanding of how branding mechanisms operate within vocational innovation systems and regional knowledge-based economic development contexts.